Root Cause Analysis of Adverse Outcomes in the Obstetrics & Gynaecology: A Prospective Study at a Tertiary Care Centre - Brijesh Narayan; Pushkar Mendiratta (Perspectives In Medical Research)
Background: Adverse events are an unwanted outcome in the routine course of patient management, with an adverse event in Obstetrics assuming even greater importance because of the extended implications for the newborn. There is limited data available on the adverse event emanating from Obstetrics and Gynaecology care in Indian population. Materials and Methods: This prospective observational study which included all the consecutive inpatients admitted with the department of Obstetrics and Gynaecology over a period of 15 months at a tertiary care centre. Incidence of adverse events were noted. Root cause analysis of the events was done and contributory factors brought out were addressed. Results: The incidence of the adverse events in our study was 2.57 % (n=90) in a total of 3503 consecutive inpatients. The most common adverse event noted in our study was surgical site infection followed by birth asphyxia. The average duration of detection of adverse event was 8.5 days, with adverse event detected in 73% patients during admission. Out of these, 98.48% had a prolonged hospital stay which averaged 5.5 days. 58% of the adverse events were grade 3 in severity while 91.1% were deemed preventable. Conclusion: Adverse events carry a giant burden with them, but their incidence can definitely be cut down by adhering to institutional protocols, checklists, increased awareness and involvement at multiple levels of hierarchy.